Influence Mechanism of Teacher Support and Parent Support on the Academic Achievement of Secondary Vocational Students - Peng, Xianjie; Sun, Xiaonan; He, Zhen (Frontiers in Psychology, 2022)
Teachers and parents are key participants in the growth of secondary vocational students, and can jointly support them. This study aimed to explore how teacher and parent support affects the academic performance of secondary vocational students, and to reveal the ‘black box’ mechanism for their interaction and relationship. We adapted a Chinese version of a scale for secondary vocational students’ perception of teacher and parent support, drawing on self-determination theory. A survey was conducted through the Chinese questionnaire platform wjx.cn, and respondents were fully informed about the research. Data were collected from 710 secondary vocational students in Shanghai, and analyzed using SPSS and AMOS. Our hypothesis model was verified, with results indicating that the support of autonomy, emotion, and ability provided by parents and teachers has a significant impact on students’ academic performance. The degree of learning engagement plays a mediating role in the relationship between support and achievement. The achievement goal orientation of students can adjust individual learning engagement, and further affect the influence of teacher and parent support on academic performance. Teacher and parent support interactively influences learning engagement. The study findings suggest that an optimization strategy is needed to promote the academic improvement of secondary vocational students to meet students’ basic psychological needs and promote cooperation between family and school. Parents and teachers should also consider the impact of learning engagement and the learning process, and offer guidance in developing an appropriate achievement goal orientation and a positive learning concept.